INTEGRATING CULTURE INTO ENGLISH LANGUAGE TEACHING: BENEFITS AND CHALLENGES - Behruzkhon Yuldoshev Behzod ugli (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the integration of culture into English Language Teaching (ELT), highlighting its importance, benefits, and challenges. Teaching English without considering cultural context can limit learners’ communicative competence and cross-cultural understanding. Incorporating cultural content in language instruction fosters motivation, authentic communication, and intercultural awareness. However, educators face challenges such as selecting appropriate materials, addressing cultural biases, and balancing language and cultural instruction. This paper discusses effective strategies and pedagogical implications for integrating culture in ELT classrooms.